Why do physicians prefer brand medicines over generic medicines in Pakistan? A quantitative approach - Masood, Imran; Saleem, Ahsan; Jamshed, Shazia (Blackwell Publishing Ltd, 2016)
Objectives Generic medicines are recommended and used largely due to their costeffectiveness. Still, physicians prefer brand medicines rather than their generic counter-parts. Therefore, the current research was aimed to evaluate the preferential attitude ofphysicians towards brand medicines over generic medicines in Pakistan.Methods This is a cross-sectional survey which was conducted in two public sectorhospitals in Bahawalpur, Punjab, Pakistan. A total of 150 physicians were interviewedusing a 17-itemed self-administered questionnaire. A 4-point Likert scale was used andresponses were measured as strongly disagree, disagree, agree and strongly agree. ACronbach’s alpha of 0.66 was obtained for all the domains. Statistical analysis wasperformed usingSPSS (version 15.0).Key ﬁndings A response rate of 84.3% was achieved. Slightly more than half of thephysicians were men (52.7%) with 64% being specialist doctors, and nearly 61.3% hadmore than 10 years of experience. Slightly more than half of the respondents agreed(n = 99; 66%) that they prefer brand medicines over generic medicines because of higherefﬁcacious potential. This was found to be statistically signiﬁcant with respect to genderwith men reported greater agreement (P < 0.001). Interestingly all the specialists (n = 96;64%; P = 0.045) agreed not to prefer generics over brand medicines because of lesserpotency.Conclusions It is concluded that physicians’ prescribing practices are signiﬁcantly affected by their lack of knowledge regarding generic medicines, patient-related factors,and by the inﬂuence of pharmaceutical advertisements.Keywords brand medicines; generic medicines; physicians; prescribing